TC2N maintains stem cell-like characteristics to accelerate lung carcinogenesis by blockade of dual specificity protein phosphatase 3 - Jing Gu; Yang-fan Lv; Ji-ying Xia; Fu-hai Bai; Ji Gong; Guang-qiang Pan; Bo Liu; Lu Huang; Qiao-nan Guo; Xiang-lin Hao (Cell & Bioscience, 2025)
Abstract Background Tandem C2 domains, nuclear (TC2N) is a protein that has been characterized to contain C2A domain, C2B domain, and a short C-terminus with a WHXL motif. In previous studies, we have uncovered the oncogenic role and mechanisms of TC2N in lung cancer: TC2N achieves this by inhibiting the p53 signaling pathway and activating the NF-kappaB signaling pathway. Beyond that, its precise function in tumorigenesis is not fully understood. Methods TC2N-engineered mice model was used to assess the effect of TC2N knockout on normal lung and urethane-induced carcinogenesis. Tumor tissues of 395 lung cancer patients were subjected to tissue microarray and further assessed the associations of TC2N expression with tumor differentiation degree. The protein levels of TC2N and stem cell markers in cell lines and tissue specimens were monitored by WB and immunohistochemistry. In vitro cell assays were performed to assess the effect of TC2N ectopic expression on the stem cell-like characteristics of lung cancer cells. The downstream signaling pathway or target molecule of TC2N was mined using a combination of transcriptomics and proteomics, and the underlying mechanism was explored by WB and co-IP assays. Results Herein, TC2N appeared to have a strong effect in promoting lung tumorigenesis caused by urethane, whereas it seemed to lose its function in the normal lung. Meanwhile, we found that the functional differences of TC2N between lung tumor and normal lung were linked to its potential role in cancer cell stemness. Function-wise, TC2N overexpression maintained stem-like properties of lung cancer cell. Mechanism-wise, TC2N upregulated the phosphorylation of EGFR, ERK, STAT3 and FAK1 to activate these signaling pathways by the inhibition of DUSP3 phosphatase via a dual mechanism. Firstly, TC2N competes with EGFR, ERK, STAT3 and FAK1 for binding to DUSP3. This competition prevents these signaling molecules from being dephosphorylated by DUSP3, resulting in their sustained activation. Secondly, TC2N bind to DUSP3 and restrict the enzyme’s ability to dephosphorylate the signaling molecules. Conclusions Overall, this study revealed a previously unknown role and mechanism of TC2N in the regulation of tumorigenesis and stemness in lung cancer cells.